Beneficial effects of a high-anthocyanin diet versus a Westernized diet on colorectal cancer risk: a systematic review - Vásquez, Alberto; Zúñiga, Paula; Torres, Keila; Quest, Andrew F. G.; Simón, Layla (Frontiers in Immunology, 2026)
IntroductionColorectal cancer (CRC) is one of the leading causes of morbidity and mortality worldwide. Its incidence has been strongly associated with dietary patterns of the Western diet (WD), which are characterized by high intakes of saturated fats, ultra-processed foods, red and processed meats, refined grains, and added sugars. In contrast, numerous studies have highlighted the potential health benefits of anthocyanins—bioactive compounds with anti-inflammatory, antioxidant, and antitumoral properties. This systematic review aimed to evaluate the effects of anthocyanin-rich diets on CRC prevention and compare them with the effects of WD.MethodsA systematic search was conducted in PubMed, Scopus, and SciELO databases following PRISMA 2020 guidelines. Search terms included: “anthocyanin” OR “anthocyanins” AND “prevention” AND “colorectal cancer” AND “Western diet” AND “effect.”ResultsSixteen studies met the inclusion criteria. Anthocyanin-rich interventions demonstrated consistent preventive effects, including the modulation of oxidative stress, suppression of oncogenic signaling pathways, induction of apoptosis in CRC cells, and restoration of gut barrier integrity and microbial diversity. Notably, these interventions exerted significant anti-inflammatory effects by downregulating pro-inflammatory cytokines, inhibiting NF-κB, and attenuating colitis-associated tumorigenesis. In contrast, Western dietary patterns were consistently associated with enhanced colonic inflammation, alterations in gut microbial composition, impairment of mucosal immune regulation, and increased colorectal tumor burden.DiscussionThis systematic review provides evidence supporting the protective role of anthocyanin-rich diets in CRC prevention. However, further research is needed to examine drug-nutrient interactions in the context of comorbidities, evaluate various sources of anthocyanins, and better understand the factors influencing their bioavailability and absorption.Systematic Review Registrationhttps://osf.io/b56yz/overview, identifier osf-registrations-b56yz-v.